Latinization of funerary epigraphy on the Iberian Peninsula: change and continuity (300 BCE to 100 CE) (Palaeohispanica. Revista sobre lenguas y culturas de la Hispania Antigua, 2024)
The paper studies the rise of epichoric funerary epigraphy in the Iberian and Celtiberian linguistic areas between the third century BCE and the first century CE in relation to the presence of Roman actors. Despite the difficulties to relate these to and establish a direct causal relation, it shown that the correlation is more than a mere coincidence.